2004
DOI: 10.1093/pcp/pch132
|View full text |Cite
|
Sign up to set email alerts
|

Two Cytokinin Receptors of Arabidopsis thaliana, CRE1/AHK4 and AHK3, Differ in their Ligand Specificity in a Bacterial Assay

Abstract: Strains of Escherichia coli that express two different cytokinin receptors of Arabidopsis thaliana, CRE1/AHK4 and AHK3, were used to study the relative sensitivity of these receptors to various cytokinins. Both receptors were most sensitive to the bases of the isoprenoid-type cytokinins trans-zeatin and isopentenyladenine but differed significantly in the recognition of other cytokinin compounds. In particular, CRE1/AHK4 recognized at 1 microm concentration only trans-zeatin while AHK3 recognized cis-zeatin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
246
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 268 publications
(267 citation statements)
references
References 28 publications
16
246
0
3
Order By: Relevance
“…Free bases and ribosides are the most physiologically active CK forms (Spichal et al, 2004;Sakakibara, 2006). Although Sakakibara (2006) suggested that cZ isomers had little or no biological activity, cZ forms were recently proven to have comparable biological activity to tZ forms in an in vitro zygotic pea embryo bioassay (Quesnelle & Emery, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Free bases and ribosides are the most physiologically active CK forms (Spichal et al, 2004;Sakakibara, 2006). Although Sakakibara (2006) suggested that cZ isomers had little or no biological activity, cZ forms were recently proven to have comparable biological activity to tZ forms in an in vitro zygotic pea embryo bioassay (Quesnelle & Emery, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…O-glycosylation has been shown to preserve the CKs from N 6 -side chain cleavage by CK oxidase (Armstrong 1994). In addition, O-glycosylated CKs can be easily converted to the active form by b-glucosidases (EC 3.2.1.21; Brzobohatý et al 1993), which explains the biological activity of O-glucosylated CKs in different bioassays, although they are not recognised by CK receptors (Spíchal et al 2004). Based on the facts mentioned above and the finding that O-glucosylated dihydrozeatin is localised in vacuoles (Fusseder and Ziegler 1988), it is believed that O-glycosylation produces an inactive, stable storage form of CKs and thus plays an important role in balancing CK levels .…”
Section: Ck Metabolismmentioning
confidence: 99%
“…Expression of CRE1/AHK4, AHK3 and AHK2-CHASE-TM (AHK2-CHASE including the two adjacent transmembrane domains) in Escherichia coli DrcsC and cps::lacZ mutant strains producing b-galactosidase in reaction to CK , and direct receptor binding assays (Romanov et al 2005) were used for molecular and biochemical characterisation of the receptors Yamada et al 2001;Spíchal et al 2004;Romanov et al 2006). It has been shown that the receptors bind isoprenoid and aromatic CKs, and also thidiazuron (a derivative of phenylurea), in a highly specific manner with K d in the nanomolar range Romanov et al 2005;Romanov et al 2006;Lomin et al 2011;Stolz et al 2011).…”
Section: Ck Perception and Signal Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peculiarities of receptor functions might be due to differences in their expression (Ueguchi et al, 2001;Higuchi et al, 2004;Nishimura et al, 2004;Stolz et al, 2011), differences in the recognition of different cytokinin compounds (Yamada et al, 2001;Spíchal et al, 2004;Romanov et al, 2006;Stolz et al, 2011), specific interactions with other proteins (Dortay et al, 2008), or differences in their subcellular localization. Current cytokinin signaling models predict that the cytokinin receptors are localized to the plasma membrane (PM), which was initially based on bioinformatic analysis of the protein sequence and analogy with sensor His kinase localization in bacteria and yeast (Inoue et al, 2001;Ueguchi et al, 2001).…”
mentioning
confidence: 99%